2012
DOI: 10.1542/peds.2011-2102
|View full text |Cite
|
Sign up to set email alerts
|

Societal Values and Policies May Curtail Preschool Children’s Physical Activity in Child Care Centers

Abstract: BACKGROUND AND OBJECTIVES: Three-fourths of US preschool-age children are in child care centers. Children are primarily sedentary in these settings, and are not meeting recommended levels of physical activity. Our objective was to identify potential barriers to children’s physical activity in child care centers. METHODS: Nine focus groups with 49 child care providers (55% African American) were assembled from 34 centers (inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 44 publications
(58 reference statements)
4
73
0
2
Order By: Relevance
“…However, there was also recognition of the need for children to be ‘school‐ready’, with academic development often deemed to be (more) important for young children .
Because even though I feel that the gross motor is something that's important for the children to experience and engage in, I don't think that their parents necessarily do … I don't think that physical activity is high on the priority list of things that schools want to necessarily provide.
…”
Section: Resultsmentioning
confidence: 99%
“…However, there was also recognition of the need for children to be ‘school‐ready’, with academic development often deemed to be (more) important for young children .
Because even though I feel that the gross motor is something that's important for the children to experience and engage in, I don't think that their parents necessarily do … I don't think that physical activity is high on the priority list of things that schools want to necessarily provide.
…”
Section: Resultsmentioning
confidence: 99%
“…Parental preferences for academics and concerns about safety have been reported by child care providers as barriers they face in promoting PA in child care. 45 Teacher training and self-efficacy in implementing APOs is another possible barrier. Although the relationship between PA and learning is gaining considerable support through research in school-aged children, 46 it is not yet as well established in preschoolers.…”
Section: Resultsmentioning
confidence: 99%
“…Biological explanations and socialisation as well as social expectations have been shown to be significant with respect to gender differences in motor skills (Campbell and Eaton 1999;Copeland et al 2012;Koda et al 2004;Mondschein et al 2000;Rossholt 2012;Walsh 2014). Research on infants has shown a small difference in motor skills favouring boys (Campbell and Eaton 1999).…”
Section: Theoretical Backgroundmentioning
confidence: 99%